Sporisorium scitamineum: A comprehensive mini-review on biology, pathogenicity, and management - Laksamana Agadhia Raharjo (Institute for Advanced Science, Social, and Sustainable Future, 2026)
Background: Sugarcane smut disease, caused by Sporisorium scitamineum, is one of the most destructive fungal diseases affecting sugarcane production in Indonesia. Although the national plantation area has expanded in recent years, productivity and sugar recovery rates remain low, hindering the achievement of sugar self-sufficiency. Understanding pathogen characteristics and improving disease management strategies are therefore critical to strengthening national sugarcane sustainability. Methods: This study employed a descriptive qualitative approach based on secondary data obtained from the Central Bureau of Statistics (BPS), the Ministry of Agriculture, and peer-reviewed scientific literature published within the last 5–10 years. The analysis covered national cultivation trends, pathogen morphology, and recent advances in chemical and biological control strategies. Findings: Indonesia’s sugarcane plantation area increased from 429,959 ha in 2018 to 494,764 ha in 2023; however, sugar recovery rates remain low (6.5–7.5%). Morphologically, S. scitamineum produces characteristic black whip-like structures containing brown teliospores, which disperse through wind, water, and infected planting materials. Disease control strategies include seed-cane treatment with systemic fungicides (e.g., flutriafol, propiconazole, triadimefon) and hot-water treatment. Biological control agents such as Trichoderma spp., Streptomyces spp., and Bacillus spp. demonstrate more than 70% suppression of pathogen growth. Recent developments emphasize integrated management combining genetic resistance, chemical protection, biological control, and molecular technologies. Conclusion: Effective management of sugarcane smut in Indonesia requires an integrated and sustainable approach that combines agronomic, chemical, biological, and molecular strategies. Strengthening disease control systems is essential to improving productivity and supporting national sugar security. Novelty/Originality of this article: This study provides an updated synthesis linking national production trends with pathogen biology and integrated control innovations. By connecting macro-level agricultural data with micro-level pathogen characteristics and emerging molecular approaches, it offers a comprehensive framework for sustainable smut disease management in Indonesia.